Circulating biomarkers in the diagnosis and prognosis of immune checkpoint inhibitor-related myocarditis: time for a risk-based approach - Murtagh, Gillian; deFilippi, Christopher; Zhao, Qiong; Barac, Ana (Frontiers in Cardiovascular Medicine, 2024)
Immune checkpoint inhibitors (ICIs) are monoclonal antibodies that block immune checkpoints and therefore activate immune cells, allowing them to recognize and attack cancer cells. ICIs have revolutionized oncology practice, but their use has been complicated by immune-related adverse events (irAEs). Of cardiovascular (CV) irAEs, ICI-related myocarditis has received significant attention due to high mortality rates, ranging from 25% to 50%, despite its overall low incidence. Establishing the early diagnosis of ICI-myocarditis is important for early initiation of steroids and consideration of hospitalization in patients who are at risk for hemodynamic compromise and need high acuity care in a tertiary setting. In this review, we summarize the diagnostic and prognostic tools for ICI-myocarditis, including electrocardiography, echocardiography, cardiac magnetic resonance imaging, with emphasis on circulating biomarkers. Cardiac troponins (cTns) are an essential component of the diagnosis of ICI-myocarditis, and we provide a summary of the recent studies that utilized different assays (cTnI vs. cTnT) and outcomes (diagnosis vs. prognosis including major adverse cardiac outcomes). With the exponential increase in ICI use across different oncology indications, there is a major need to include biomarkers in risk stratification to guide diagnosis and treatment. Our review proposes a framework for future multisite registries, including cTn evaluation at baseline and at the time of irAE suspicion, with development of central biobanking to allow head-to-head evaluation and clinical validation of different biomarker assays in ICI-myocarditis. This approach, with the inclusion of CV biomarkers into clinical and pragmatic oncology trials, holds promise to improve the early recognition and management of ICI-myocarditis and CV irAEs, thus leading to better outcomes.